Uma proposta para o uso do software Winplot no ensino da Matemática para estudantes do ensino médio do IFMT, campus Cuiabá - Pereira, Willian de Souza (2015)
This study has as main aim to present the software Winplot as an educational resource in order to favor the understanding of mathematical contents, more specifically, the bidimensional approach. In order to carry out this study, the theoretical framework was guided by state of the art concerning the ICTs used in the mathematical classes and the reflections included in The Brazilian National Curricular Parameters for High School. In order to achieve the proposed objectives, it was built educational activities mediated by the software Winplot, aimed at charting the figures of bi-dimensional graphics offered for two classes of students of the 2nd year of high school at the Federal Institute of Mato Grosso (IFMT). The main essence of the educational proposal for the students is not only to present the importance of using Winplot software as a teaching resource in the application of the content of the functions, but also, to make possible for the students to experience new ways of considering the use of the computer associated to the proposed activities. However, it is essential that the educators may have necessary qualifications aimed at the construction of educational activities mediated by the software Winplot to be done according to the profile of each class. It is hoped that this dissertation may generate more knowledge, broaden the dialogue between the IFMT Math educators, promoting reflections towards appropriate mathematical proposals aimed at the real needs of students.